2020
DOI: 10.1136/bcr-2019-233452
|View full text |Cite
|
Sign up to set email alerts
|

Prone positioning in a patient with fat embolism syndrome presenting as diffuse alveolar haemorrhage: new perspective

Abstract: Diffuse alveolar haemorrhage (DAH) is a rare complication of fat embolism syndrome leading to severe hypoxaemia due to the effusion of blood into the alveoli from the damaged pulmonary microvasculature. The management is usually supportive with patients being nursed in supine position. The use of prone position ventilation in a DAH has rarely been reported before. We report an interesting case of a 26-year-old male patient diagnosed with DAH caused by fat embolism in whom prone position ventilation improved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Albumin administration has been shown to be helpful, presumably because of its ability to bind free fatty acids [ 1 , 2 ]. Steroid use has also been reported [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin administration has been shown to be helpful, presumably because of its ability to bind free fatty acids [ 1 , 2 ]. Steroid use has also been reported [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial or mild FES is treated with supplemental oxygen, titrated to maintain normal PaO2. FES that progresses to respiratory failure requires mechanical ventilation [8,9]. Secondly, in patients exhibiting neurologic complications, neurologic status should be closely monitored via frequent Glasgow Coma Scale assessments and serial neurologic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] The use of lung-protective ventilation and prone positioning is reported to help patients with ARDS caused by FES. [ 3 ] However, in FES cases with unstable pelvic fractures, comminuted vertebral fractures, or dislocated femoral fractures, it is necessary to achieve bone stability by performing early rigid internal fixation before placing the patient in the prone position. Numerous studies have shown that early definitive long bone fracture fixation is important in the prevention of respiratory complications.…”
Section: Introductionmentioning
confidence: 99%